Controls on the breach geometry and flood hydrograph during overtopping of noncohesive earthen dams. Issue 8 (30th August 2015) - Walder, Joseph S.; Iverson, Richard M.; Godt, Jonathan W.; Logan, Matthew; Solovitz, Stephen A.
Abstract Overtopping failure of noncohesive earthen dams was investigated in 13 large‐scale experiments with dams built of compacted, damp, fine‐grained sand. Breaching was initiated by cutting a notch across the dam crest and allowing water escaping from a finite upstream reservoir to form its own channel. The channel developed a stepped profile, and upstream migration of the steps, which coalesced into a headcut, led to the establishment of hydraulic control (critical flow) at the channel head, or breach crest, an arcuate erosional feature that functions hydraulically as a weir. Novel photogrammetric methods, along with underwater videography, revealed that the retreating headcut maintained a slope near the angle of friction of the sand, while the cross section at the breach crest maintained a geometrically similar shape through time. That cross‐sectional shape was nearly unaffected by slope failures, contrary to the assumption in many models of dam breaching. Flood hydrographs were quite reproducible—for sets of dams ranging in height from 0.55 m to 0.98 m—when the time datum was chosen as the time that the migrating headcut intersected the breach crest. Peak discharge increased almost linearly as a function of initial dam height. Early‐time variability between flood hydrographs for nominally identical dams is probably a reflection of subtle experiment‐to‐experiment differences in groundwater hydrology and the interaction between surface water and groundwater.